Dynamic fabrication of microfluidic systems for particles separation based on optical projection lithography. - Sun, Lujing; Yang, Wenguang; Chu, Honghui; Yang, Rendi; Yu, Haibo (Biomedical Microdevices, 2020)
Microfluidic systems are widely used for applications in biology, medicine and chemistry. Particles separation by microfluidics is a scientific subject that requires ongoing research efforts. In this article, we demonstrate a micropillar-based particles separator fabricated using digital micromirror device (DMD)-based optical projection lithography from the perspectives of theory, design, simulation and experiments. Micropillars can be fabricated with customized shapes and sizes which shows high flexible and efficient. The particles separator employs the physical separation of a cylindrical array, a rectangular array, or a triangular array to separate particles. The simulation and experiment results indicate that the device with different micropillars could achieve separation of 20 and 200 μm polystyrene microspheres. Furthermore, the separation efficiency depended on flow rate and the shape of micropillars. All the results can be used to support the redesign of microfluidic structures to address particles separation needs.